Snow Reliability and Water Availability for Snowmaking in the Ski resorts of the Isère Département (French Alps), Under Current and Future Climate Conditions - Martin Gerbaux; Pierre Spandre; Hugues François; Emmanuelle George; Samuel Morin (Revue de Géographie Alpine)
This study presents the evolution of the snow reliability in the 24 alpine ski resorts of the Isère département (Northern French Alps, around Grenoble) over the last decades and its projection into the 21st century, taking into account grooming and snowmaking. The water demand for snowmaking is calculated and can be compared with hydrological simulations of water resource availability, under current and future climate conditions. Over the recent period, snowmaking has significantly improved the snow conditions in seasons with a natural snow deficit. For the middle of the 21st century, climate projections indicate that the expected evolution of snowmaking infrastructure by 2025 should make it possible to stabilize the snow reliability in seasons characterized by a deficit of natural snowfall. At a constant equipment rate, the evolution of water demand due to climate change is of the order of +15% on average in Isère between the recent period and the middle of the 21st century. The study shows that the pressure on water resources appears to not be the most critical point for the implementation of snowmaking, at the scale of the catchment basins in which the Isère ski resorts are located.